Uterine rupture in pregnancy after previous laparoscopic myomectomy: an insidious presentation - Veloso,Helena (2021)
Abstract Uterine rupture in pregnancy is a rare complication that can be life-threatening for the mother and fetus. The severity of the outcomes depends on factors such as size and location of the rupture and speed of intervention. We report a case of uterine rupture at a 26 weeks twins' gestation in a woman with previous laparoscopic myomectomy. She was admitted to the emergency department with abdominal pain and urinary frequency and a urinary tract infection was diagnosed. One week later, she was re-admitted with worsening abdominal pain and hemodynamic instability. An hemoperitoneum and uterine rupture were diagnosed during an emergency laparotomy. The mother survived with no complications. The neonates died on the first day due to complications associated with extreme prematurity. This case outlines that given the severity of a uterine rupture and the nonspecific symptoms associated, a high index of suspicion is mandatory in order to avoid poor outcomes.